2004
DOI: 10.1128/cdli.11.4.792-794.2004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Severe Acute Respiratory Syndrome (SARS) Coronavirus-Specific Antibodies in 271 Laboratory-Confirmed Cases of SARS

Abstract: The sensitivities and specificities of an immunofluorescence assay and an enzyme immunoassay for detection of antibodies specific for severe acute respiratory syndrome coronavirus (SARS-CoV) were compared for 148 laboratory-confirmed SARS cases. The appearance and persistence of SARS-CoV-specific antibodies were assessed, with immunoglobulin G detected in 59% of samples collected within 14 days and persisting for 60 to 95 days after the onset of illness. (2-4, 7, 9, 10), although data on the performance of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…Of the 148 SARS-CoV RT-PCR positive samples, SARS-CoV IgG was detected in 145 (98%) and SARS-CoV IgM in 117 (79%) using IFA. 12 There were 33/304 (10.9%) that were negative on SARS testing. An alternative laboratory diagnosis was made in 27/33, of which the most common were acute influenza B (13 cases) and Klebsiella pneumoniae infection (nine cases).…”
Section: Resultsmentioning
confidence: 98%
“…Of the 148 SARS-CoV RT-PCR positive samples, SARS-CoV IgG was detected in 145 (98%) and SARS-CoV IgM in 117 (79%) using IFA. 12 There were 33/304 (10.9%) that were negative on SARS testing. An alternative laboratory diagnosis was made in 27/33, of which the most common were acute influenza B (13 cases) and Klebsiella pneumoniae infection (nine cases).…”
Section: Resultsmentioning
confidence: 98%
“…Second, we did not use any antibody test other than IFA, such as an enzyme-linked immunosorbent assay, to determine the antibody response and compare the results with those determined by IFA. However, some previous studies have demonstrated that the antibody responses determined by IFA and enzyme-linked immunosorbent assays were similar (4,6). Third, only 29.5% of SARS patients who survived and were treated in our hospital were followed for more than 1 year and enrolled in this study.…”
mentioning
confidence: 99%
“…Prior studies pointed out that (i) the specific antibody to SARS-CoV appears as early as 9 days after the disease onset and a high level of the antibody can last for 1 to 2 months (3, 9), (ii) IgM and IgG to SARS-CoV appear at almost the same time (4,6,14), (iii) the peak IgG titer is usually noted 4 to 12 weeks after the disease onset (7,14), and (iv) the IgM to SARS-CoV is usually undetectable 180 days after the disease onset (14). Our present study demonstrated similar results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent levels of SARS-CoV IgG have been detected in SARS cases for several months and up to 2 years after disease onset (4,11,12,19,21). In this study, serum samples from 48 SARS patients from Vietnam and the United States were collected 221 to 735 days (44 from days 221 to 250; 4 from days 633 to 735) after the onset of illness and tested for the presence of SARS-CoV-and N-and S-protein-specific IgG by ELISA.…”
mentioning
confidence: 99%